Organic chilli production in the North Eastern Hill Region, India: value chain analysis for doubling farmers’ income - Ram Singh; S Passah; N Anandkumar Singh; S M Feroze; Larinsangpuii; A Anuradha Devi; Shiv Kumar; Abhimanyu Jhahjria (Agricultural Economics Research Review, 2023)
Cultivars of spices, like chilli, that are local to the North Eastern Hill Region (NEHR) of India are famous for their chemical properties. We examine the economics of chilli cultivation (organic and conventional), supply chain arrangements, and value addition options. We find that chilli cultivation is profitable and organic cultivation more so. The value addition analysis suggests the technological interventions that would add value to the local cultivars. Farmers’ income can be increased by organically cultivating chilli and adding value.